Análise da estrutura e do funcionamento de conselhos de administração na perspectiva de conselheiros: (des)construindo as racionalidades dos discursos dos atores - Kelen Vanzin Moura da Silva (2013)
This research aims to identify the rationales of the board members by their speeches in particular about the recommendations on corporate governance These are addressed from the perspective of corporate rhetoric and evaluated in relation to the recommendations of the code of IBGC (2009) and the OECD (2004) principles in order to establish sameness and divergence between the recommendations and practices. It was used for those, the theoretical framework that understands the bounded rationality, the problem of agency, transaction costs. power relations and also models of corporate governance. The research is qualitative in nature and is divided into two phases conducted throughout 2012. The first one was developed based on research on the websites of 125 companies listed on the Novo Mercado (New Market - free translation) and others 38 ones which make up the Level 1 of Bovespas corporate governance in order to ground the analyzes and support the identification of institutionalized practices. The choice of such levels coincided with the classification of companies that operate in the vast majority of the directors interviewed, which comprise the second stage of this research. The outside research was developed in three state capitals, S50 Paulo, Belo Horizonte and Curitiba. The data analysis was elaborated according to qualitative proposal Creswell (2007. 2009), operationalized using NVivo software for the categorization of the information collected particularly with respect to compliance with the corporate governance recommendations. The interviews analysis indicates that the rationales underlying the speeches of the directors interviewed reinforce the problems coming from the influence of concentrated ownership structure, in particular regarding compliance with the recommendations of corporate governance. They appear in the speeches of the directors interviewed, but in practice, there is a strong influence of the financial logic for decision making. Therefore, it was found that the recommendations of corporate governance codes are the most widespread in the formal (speech). Already in practice contradictions emerge that reflect a real gap between what is preached and what is shown performing. Observed in research on the websites of the companies listed on the Novo Mercado and Level 1 that, although there has been an increase in the availability of information, blanks are appeared in relation to the processes of election of directors, the identification of the independent at the time of the mandate, the internal regulations and codes of conduct. At the end of the study, might questioning the possibility of independent director to effectively sustain this condition due to the lack of references to limit his time in office as an advisor, the real possibilities of fulfilling the requirements set out in the code of IBGC (2009) and OECD Principles (2004), and especially with regard to its ability to maintain relief on the interests of those indicated. Regarding the corporate governance models that underlie the structure and functioning of the CA's, there was a prevalence of the financial model, although there have been some indications of the model stakeholders, specifically in experiments reported by counselors as favorable to the labor force participation and understood as a possibility for enriching the boards.